Maqasid Shariah Practices in business (Study of UD Flipper Perak Home Industry in East Java, East Java - Arivatu Ni’mati Rahmatika; Uswatun Hasanah; Amin Awal Amarudin; Fitri Zaelina (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2019)
The purpose of Islam is to achieve the benefit, one of which is the benefit that is dharuriyat. Covered in the Shariah maqasid, making this study a discussion related to the practice of the shariah maqasid in the business world that is currently increasing. Different types of businesses make economic activity for Muslims diverse. This study aims to describe in detail and comprehensively the practice of maqasid shariah in the home industry in the city of Jombang. The researcher used a qualitative approach with exploratory, literary and phenomenological methods, the data in this study were primary data obtained from interviews with stakeholders, while secondary data were obtained from literature studies for the basic concepts in this study. The results of this study are the practice of maqashid shariah in business activities in the home industry, namely the maintenance of religion is at the provision of time for praying, guarding the mind in the form of employee training, guarding offspring in the form of maternity leave, the maintenance of life in the form of the environment and safe and non-threatening business production tools lives, guarding assets in the form of increased income of employees after working in the home industry.